Financing Agricultural Practices of Khush Tepa Canal through Agriculture Sukuk - Omari, Najeebullah (Journal of Natural Sciences – Kabul University, 2024)
Afghanistan, our beloved country, is an agricultural nation blessed with fertile lands. Strengthening the agricultural sector is essential to achieving self-sufficiency. To modernize agriculture in the country, several Islamic economic mechanisms have been proposed, drawing inspiration from successful implementations in the contemporary world, particularly in Islamic nations. One such mechanism is sukuk. Sukuk are financial instruments designed for the banking and financial sector, offering security, safety, and guaranteed returns. These instruments are tradable, enabling the mobilization of idle funds from the commercial market and injecting them into the economic cycle. In agriculture, specific types of sukuk, such as Sharecropping Certificates (Muzara’ah Sukuk), Irrigation Certificates (Musaqat Sukuk), and Agricultural Certificates (Mugharasah Sukuk), are utilized to finance and advance agricultural practices. This article explores the adaptation of these types of sukuk within the framework of Islamic jurisprudence, analyzing their practical and technical applications in the context of Afghanistan's economic and agricultural landscape. The focus is on financing agricultural operations around the Khush Tepa irrigation scheme. Under this mechanism, various stakeholders in the agricultural sector—such as agricultural banks, companies, and relevant government or private entities—can issue sukuk. These entities can attract investments, lease or purchase lands surrounding the canal, and use the proceeds to enhance agricultural operations. Income generated from these activities, along with profits, is distributed among sukuk holders in proportion to their investment, based on pre-agreed terms outlined in the sukuk prospectus.